Determinantes do Desempenho dos Participantes da Prova do Enem: Evidências para o Rio Grande Do Sul (Desenvolvimento em Questão, 2020)
The study of the difference in school performance between public and private schools is important for public policies, especially those that relate social policies for entering higher education. In this way, the article aims to investigate the occurrence of differences between public and private education, in the state of Rio Grande do Sul, based on the performance of students in the National High School Exam, in 2017. For that it was applied quantile regression modeling decomposed into quartiles is made to the conditional distribution of proficiency. The results proved to be favorable to the performance of students from private schools, in an increasing way, for the quartiles, and who have better family socioeconomic conditions such as income and a mother with higher education. Evidence that demands public policies to equalize the possibilities of access to higher education as a way to minimize the growing educational inequalities
Keywords: school performance, ENEM, quantile regression